KEPEMIMPINAN MANAJERIAL DAN AKUNTABILITAS KERJA: TINJAUAN LITERATUR TERHADAP PENGARUH PIMPINAN TERHADAP EFEKTIVITAS ORGANISASI - Eliagus Telaumbanua; Al-Amin (BORJUIS: JURNAL OF ECONOMY, 2025)
The results of this study indicate that managerial leadership has a significant influence on organisational effectiveness. A leader who is able to formulate a clear vision, direct resources optimally, and build effective communication can improve individual and team performance. Appropriate leadership styles—such as transformational, participative, or situational—have been proven to motivate employees, foster collaboration, and strengthen organisational adaptation to environmental changes, which ultimately promotes the efficient and sustainable achievement of strategic goals. In addition to leadership, work accountability has also been proven to be a key factor supporting organisational effectiveness. A strong accountability culture ensures that every member understands their roles and responsibilities, works according to established standards, and is ready to be evaluated objectively. The reciprocal relationship between leadership and accountability is clear: leaders establish and maintain accountability mechanisms, while effective accountability systems help strengthen credibility and trust in leadership. The synergy between the two creates a transparent, disciplined, and highly integrity-driven organisation. Overall, the findings of this study confirm that managerial leadership and work accountability are two inseparable pillars in efforts to improve organisational effectiveness. The practical implication is that organisations need to develop leadership competencies while building a fair, transparent, and consistent accountability system. The combination of visionary leadership and a strong accountability culture will strengthen organisational competitiveness, enhance stakeholder trust, and ensure sustainable performance amid increasingly complex environmental dynamics.